Herbivore‐induced plant volatiles provide associational resistance against an ovipositing herbivore. (14th December 2012) - Zakir, Ali; Sadek, Medhat M.; Bengtsson, Marie; Hansson, Bill S.; Witzgall, Peter; Anderson, Peter
Summary: Plants produce herbivore‐induced plant volatiles (HIPVs) in response to damage by herbivores. Although HIPVs are known to enhance plant resistance by affecting herbivore host plant preferences and by attracting natural enemies, little is known about the role of HIPVs on the resistance of neighbouring plants and the mechanism behind this associational resistance. This study examined the effect of HIPVs from herbivore‐damaged host plants (alfalfa ( Medicago sativa ), clover ( Trifolium alexandrinum ) and cotton ( Gossypium hirsutum )) on oviposition by Egyptian cotton leafworm ( Spodoptera littoralis ) (Lepidoptera: Noctuidae) on neighbouring, undamaged host plants. There was a significant reduction in oviposition by S. littoralis on undamaged plants adjacent to herbivore‐damaged cotton plants under both field and laboratory conditions. The results showed that the associational resistance by HIPVs depends on direct effects on oviposition behaviour in S. littoralis . There were also indications that other mechanisms may be involved. Associational resistance via HIPVs was not observed for all plant species tested. Emission of HIPVs from damaged cotton increased the resistance of undamaged cotton and alfalfa plants to oviposition by S. littoralis, but HIPVs from damaged alfalfa and clover neighbours did not provide resistance to undamaged cotton plants. Synthesis . Our results suggest that the presence of HIPV‐emitting plant neighbours can reduce herbivory on undamaged plants and enhance plant resistance by affecting oviposition behaviour in insect herbivores. Abstract : Herbivore‐induced volatiles (HIPVs) from cotton plants were found to provide associational resistance by affecting the oviposition behaviour in the moth Spodoptera littoralis . Our results suggest that the presence of HIPV‐emitting plant neighbours can reduce herbivory on undamaged plants and enhance plant resistance by reducing insect herbivore attack.